Lipopolysaccharide‐Induced Bone Loss in Rodent Models: A Systematic Review and Meta‐Analysis. (5th December 2022) - Bott, Kirsten N.; Feldman, Evelyn; de Souza, Russell J.; Comelli, Elena M.; Klentrou, Panagiota; Peters, Sandra J.; Ward, Wendy E.
ABSTRACT: Osteoporosis has traditionally been characterized by underlying endocrine mechanisms, though evidence indicates a role of inflammation in its pathophysiology. Lipopolysaccharide (LPS), a component of gram‐negative bacteria that reside in the intestines, can be released into circulation and stimulate the immune system, upregulating bone resorption. Exogenous LPS is used in rodent models to study the effect of systemic inflammation on bone, and to date a variety of different doses, routes, and durations of LPS administration have been used. The study objective was to determine whether systemic administration of LPS induced inflammatory bone loss in rodent models. A systematic search of Medline and four other databases resulted in a total of 110 studies that met the inclusion criteria. Pooled standardized mean differences (SMDs) and corresponding 95% confidence intervals (CI) with a random‐effects meta‐analyses were used for bone volume fraction (BV/TV) and volumetric bone mineral density (vBMD). Heterogeneity was quantified using the I 2 statistic. Shorter‐term (<2 weeks) and longer‐term (>2 weeks) LPS interventions were analyzed separately because of intractable study design differences. BV/TV was significantly reduced in both shorter‐term (SMD = −3.79%, 95% CI [−4.20, −3.38], I 2 62%; p  < 0.01) and longer‐term (SMD = −1.50%, 95% CI [−2.00, −1.00], I 2 78%; p  < 0.01) studies. vBMD was also reduced in both shorter‐term (SMD = −3.11%, 95% CI [−3.78, −2.44]; I 2 72%; p  < 0.01) and longer‐term (SMD = −3.49%, 95% CI [−4.94, −2.04], I 2 82%; p  < 0.01) studies. In both groups, regardless of duration, LPS negatively impacted trabecular bone structure but not cortical bone structure, and an upregulation in bone resorption demonstrated by bone cell staining and serum biomarkers was reported. This suggests systemically delivered exogenous LPS in rodents is a viable model for studying inflammatory bone loss, particularly in trabecular bone. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).